Aluminum Alkyls as Highly Active Catalytic Chain Transfer Agents. Issue 1 (7th January 2020) - Ewart, Sean; Konstantinov, Ivan; Karjala, Teresa; Baugh, Dan; Munjal, Sarat
Abstract: During the production of free radical initiated low‐density polyethylene (LDPE), it was discovered that the addition of low levels of alkyl aluminum compounds caused the molecular weight of the LDPE to drop precipitously. Further investigation demonstrated that aluminum‐alkyl compounds are among the most effective chain transfer agents ever utilized. It was also shown that polymer chains, which transfer to Al alkyl species, contain almost exclusively vinyl terminated end groups. A catalytic chain transfer mechanism is proposed in which chain transfer occurs from a growing polymer chain to an aluminum center followed by beta hydride elimination to produce a vinyl terminated polymer chain and a new aluminum hydride bond. This new aluminum hydride bond can then undergo further chain transfer reactions. This is the first time such a catalytic chain transfer mechanism has been reported. As little as 10–20 mol ppm aluminum alkyl species decreased the degree of polymerization by a factor of 2 resulting in chain transfer constant ( C s ) values as high as 1000–2000. Density functional theory (DFT) study elucidated the catalytic cycle of triethylaluminum (TEA). It is discovered that, depending on the reaction conditions, TEA can serve as a conventional as well as catalytic chain transfer agent. Abstract : This article describes the experimental and computational study of a novel class of aluminum alkyls as chain transfer agents (CTAs) for use in low‐density polyethylene (LDPE) production. These CTAs are highly active and catalytic in nature. They provide a unique way to control the molecular weight of LDPE and can be used in the design of the next generation polymer materials.